A simple interferometric method to measure the calibration factor and displacement amplification in piezoelectric flextensional actuators - Barbosa, Francisco de Assis Andrade [UNESP]; Nader, Gilder [UNESP]; Higuti, Ricardo Tokio [UNESP]; Kitano, Cláudio; Silva, Emílio Carlos Nelli (Sociedade Brasileira de Automática, 2010)
A interferometria laser constitui uma técnica consagrada para caracterizar atuadores piezoelétricos. Neste trabalho, utilizase um interferômetro de Michelson de baixo custo para mensurar o fator de calibração e a amplificação de deslocamento de um novo atuador piezoelétrico flextensional (APF), projetado através da técnica de otimização topológica. Um método simples, baseado na excitação do APF com sinal triangulare com baixa profundidade de modulação de fase óptica, permite realizara calibração absolutado interferômetro. Deslocamentos do APF para várias tensões de excitação são mensurados e a amplificação do deslocamento da piezocerâmica é determinada. A linearidade e a resposta em frequência do APF, até a frequência de 20 kHz, são avaliadas

Laser interferometry is a well-established technique for the characterization of piezoelectric actuators. In this work, by using a low cost Michelson interferometer, the measurement of the calibration factor and the displacement amplification of a novel piezoelectric flextensional actuator (PFA), designed by using the topology optimization method, is performed. A simple method, based on small phase modulation depth when the PFA is driven by a triangular waveform, allows the absolute interferometer calibration. The free-displacement of the PFA for various drive voltages is measured and the displacement amplification is determined. The linearity and frequencyresponse of the PFA are evaluated up to 20 kHz
Um método interferométrico simples para mensurar o fator de calibração e a amplificação do deslocamento em atuadores piezoelétricos flextensionais
Keywords: Interferômetros; Medição de deslocamento; Atuador piezoelétrico flextensional; Cerâmica PZT; Interferometers; Displacement measurement; Piezoelectric flextensional actuators; PZT ceramics